Comparison of Twitter Users' Perception of Content Marketing Effectiveness and Service Quality in Two Online Transportation - Adelia Salsabila Rachma; Rita Ambarwati; Muhammad Yani (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
Along with digital developments, traditional transportation is transformed into online transportation. Online transportation service provider companies that are currently being used by the public are Gojek and Grab. Behind the convenience and speed of ordering a motorcycle taxi via the application, online transportation users still complain about the services and offers provided. This study aims to find out and analyze the perceptions of online transportation users who are also users of social media, especially Twitter, regarding service performance and marketing content that has been carried out by Gojek and Grab. The research method used is a qualitative research method with analysis using Social Network Analysis (SNA) to identify, measure, and analyze the perceptions of Gojek and Grab users on the Twitter application. The study results show that people's perceptions of using Gojek and Grab for online transportation have a significant positive effect. This is shown by the acquisition of visualized data, which provides evidence that there are many interactions between Twitter users about Gojek and Grab. Public perceptions as consumers, both destructive and good perceptions, are proven to influence views of online transportation.